Platelet Function: Acute versus Chronic Responses to Physical Exercise: A Review - Skouras, Apostolos Z.; Tsantes, Andreas G.; Koulouvaris, Panagiotis (Seminars in Thrombosis and Hemostasis, 2025)
Platelets play a central role in primary hemostasis and arterial thrombosis, and accumulating evidence suggests that physical exercise can modulate platelet function. Acute vigorous or exhaustive bouts commonly produce transient thrombocytosis, enhanced aggregation and degranulation (e.g., P-selectin, β-TG, and PF4), increased thromboxane generation, and short-lived shifts toward hypercoagulability; these responses seem to scale with exercise intensity, adrenergic drive, and shear stress and may be amplified in untrained or high-risk individuals. By contrast, repeated training across modalities (aerobic, resistance, and high-intensity interval) generally lowers resting platelet reactivity, augments endothelial nitric oxide (NO) bioavailability, improves redox balance, and strengthens fibrinolytic capacity. These favorable adaptations may diminish with detraining, suggesting that the platelet-modulating effects of exercise are dynamic and contingent on consistent training exposure. In this review, we examine the association between platelet function and distinct exercise modalities, including aerobic, resistance, and high-intensity training, influence. We compare exercise modalities, intensities, and fitness states and consider major methodological sources of heterogeneity (assay selection, sampling timing, exercise prescription, and inter-individual variability) that complicate interpretation. Clinically, regularly performed, appropriately progressed exercise appears net favorable for hemostatic balance, whereas unaccustomed extreme exertion in high-risk individuals should be approached with preparation and caution. Better-standardized protocols and biomarker-informed trials are needed to refine exercise prescriptions for reducing thrombotic risk.
Keywords: cardiovascular disease; exercise; hemostasis; physical activity; platelets